2010
DOI: 10.1063/1.3284647
|View full text |Cite
|
Sign up to set email alerts
|

Micro-Raman spectroscopy of Si nanowires: Influence of diameter and temperature

Abstract: Raman spectroscopy provides nondestructive information about nanoscaled semiconductors by modeling the phonon confinement effect. However, the Raman spectrum is also sensitive to the temperature, which can mix with the size effects borrowing the interpretation of the Raman spectrum. We present an analysis of the Raman spectra of Si nanowires (NWs). The influence of the excitation conditions and the temperature increase in the NWs are discussed. The interpretation of the data is supported by the calculation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 10 publications
1
28
0
Order By: Relevance
“…In previous reports was demonstrated that heating induced by the Raman beam has a relevant contribution to the Raman spectrum of NWs (8)(9)(10). The Raman spectrum can be acquired over a bundle of NWs, or can be acquired on individual NWs conveniently separated from the substrate, deposited and localized in the grid holder in the scanning electron microscope (SEM).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In previous reports was demonstrated that heating induced by the Raman beam has a relevant contribution to the Raman spectrum of NWs (8)(9)(10). The Raman spectrum can be acquired over a bundle of NWs, or can be acquired on individual NWs conveniently separated from the substrate, deposited and localized in the grid holder in the scanning electron microscope (SEM).…”
Section: Resultsmentioning
confidence: 99%
“…The analysis of the Raman spectrum of nanosized structures is based on the phenomenological confinement model introduced by Ley et al (3), further extended to NWs by Campbell et al (4). In the case of Si NWs there is a great amount of controversy because of the discrepancies between the expected and measured lineshapes of the one phonon bands, which does not permit to provide accurate values for the NWs diameter (6)(7)(8)(9)(10). The one phonon Raman lineshape can be contributed by other factors, e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 has been adjusted considering four NWs with diameters of 20, 30, 40 and 100 um (see the inset in Fig. 1), which according to our calculations reach temperatures of 400, 325, 250 and 150°C, respectively, obtaining a reasonable fitting of the experimental data [12].…”
Section: Yjmentioning
confidence: 99%
“…On the other hand, NWs are systems with reduced thermal conductivity, orders of magnitude below the bulk thermal conductivity (4,5); furthermore, they stand in air, which makes very difficult the evacuation of heat, which is extensible to devices under operation. NWs under the excitation with a focused laser beam can reach non negligible temperatures, which is crucial for interpreting the Raman and PL spectra (6,7). These techniques can be used as contact less probes for measuring the thermal thermal conductivity of NWs; X.F.Liu et al measured the thermal conductivity of CdS NWs using microPL spectroscopy (8), and M. Soini et al measured the thermal conductivity of GaAs NWs using micro-Raman spectroscopy (9).…”
Section: Introductionmentioning
confidence: 99%